Nanosheet-Assembled Hematite Spheres for Adsorption of Cr(VI) - Wang, Weiwei; Yao, Jialiang (Asian Journal of Chemistry, 2014)
Fabricating complex architectures with small building blocks is an effective method to increase its surface area and improve its performance in removal of heavy metal. However, the techniques for preparing iron oxide complex structures still remain a challenge because of the rapid hydrolysis of Fe(III). We prepared a-Fe2O3 hierarchical spheres with nanosheet building units by using ascorbic acid to control the concentration and speed of hydrolysis of Fe(III). The phase, morphology and size of samples were characterized by X-ray powder diffraction and scanning electron microscopy. Experimental results showed that ascorbic acid had an important effect on the morphology and size of samples. Their adsorption activities were determined using Cr(VI) present in aqueous solution. The adsorption process fitted to Freundlich isotherm models for a-Fe2O3 hierarchical spheres. The adsorption kinetics followed pseudo-second-order rate kinetic model and a-Fe2O3 hierarchical spheres exhibited a better Cr(VI) adsorption property.